The Effect of Traditional Games and Free play on Motor Skills of Preschool Children - Tan, Jernice SY; Nonis, Karen; Chan, L.Y. (2020)
A child’s play is critical to whole child development. However, literature related to how traditional games and unstructured free play is limited. This study investigated if traditional games and free play could influence the motor skills of preschool children. One hundred and ninety-two children (Traditional Group: n = 114, M age = 4.5 & Play Group: n = 78, M age: 4.7) were recruited. Traditional Group played five types of traditional games while Play Group had free play over 20 sessions in 5 weeks. The MABC-2 was used to assess their motor skills. Data were analysed in three groups: All, performing 30 and Underperforming 30. The results showed that all participants made significant improvements in balance and overall motor skills with either traditional games or free play. Within the Performing 30 category, the Traditional Group performed significantly better in manual dexterity and overall motor skills as compared with the Play Group. However, both groups improved significantly in manual dexterity, balance abilities and overall motor skills within the Underperforming 30 category. This suggested that irrespective of structured traditional games or unstructured free play, child’s play has positive benefits on the development of motor skills especially for children with poorer motor skills.